$\sqrt[3]{0 \cdot 064}=\sqrt[3]{0 \cdot 027}+\sqrt[3]{?}$
2 Votes
2 Votes

$\sqrt[3]{0 \cdot 064}=\sqrt[3]{0 \cdot 027}+\sqrt[3]{?}$

in Mathematics
by
7.2k Points

1 Answer

2 Votes
2 Votes
 
Best Answer

Solution:

 $\sqrt[3]{0 \cdot 064}=\sqrt[3]{0 \cdot 027}+\sqrt[3]{?}$

$$

\begin{array}{l}

\Rightarrow \quad 0 \cdot 4=0 \cdot 3+\sqrt[3]{?} \\

\Rightarrow \quad \sqrt[3]{?}=0 \cdot 4-0 \cdot 3=0 \cdot 1 \\

\therefore \quad ?=(0 \cdot 1)^{3}=0 \cdot 001 ; \text { Ans. }

\end{array}

$$

by
7.2k Points

Related Questions

2 Votes
2 Votes
1 Answer 4 Views
2 Votes
2 Votes
0 Answers 9 Views
2 Votes
2 Votes
0 Answers 6 Views